2005
DOI: 10.1160/th04-12-0823
|View full text |Cite
|
Sign up to set email alerts
|

Local delivery of 17β-estradiol improves reendothelialization and decreases inflammation after coronary stenting in a porcine model

Abstract: In the current study, we investigated the effect of local intravascular delivery of 17beta-estradiol (17beta-E) on subsequent in-stent neointimal hyperplasia. Twenty-seven stents were implanted in coronary arteries of juvenile swine. Coronary arteries were randomized to local treatment with 17beta-E or no drug therapy (control-vehicle treated). Twenty-eight days post-treatment, angiographic images revealed an improved minimal lumen diameter (2.2 +/- 0.2 vs. 1.3 +/- 0.2 mm, P < 0.005) and a reduction of late lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…Therefore, new strategies are required for better long-term prognosis and restenosis prevention. Our group previously demonstrated that local delivery of a single bolus of 17βE reduced restenosis after PTCA and stent implantation by reducing PCNA-positive VSMC numbers and the inflammation process [13, 14]. In this study, we reported a significant difference in the ratio of collagen type III to type I in the neointima between PTCA (where collagen type I predominates) and stent implantation (mostly collagen type III).…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…Therefore, new strategies are required for better long-term prognosis and restenosis prevention. Our group previously demonstrated that local delivery of a single bolus of 17βE reduced restenosis after PTCA and stent implantation by reducing PCNA-positive VSMC numbers and the inflammation process [13, 14]. In this study, we reported a significant difference in the ratio of collagen type III to type I in the neointima between PTCA (where collagen type I predominates) and stent implantation (mostly collagen type III).…”
Section: Discussionmentioning
confidence: 49%
“…When compared with control vehicle-treated groups, arterial segments treated with local delivery of 17βE showed a significant reduction of morphometric area stenosis, from 30 to 16% for PTCA and from 71 to 55% for stent, which represented a decrease of 47 and 23%, respectively (table 1). Previous work from our laboratory has demonstrated that local delivery of 17βE significantly decreases the number of proliferating cell nuclear antigen (PCNA)-positive VSMC after PTCA or stent implantation [13, 14]. Based on these results, we evaluated VSMC density in the media and the neointima at post-procedure day 28.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…33 Neointima formation after acute endovascular injury is inhibited by E 2 supplementation and different mechanisms have been proposed including inhibition of SMC migration and proliferation, and stimulation of reendothelialization. 12,38 Interestingly, it was suggested by an in vitro study that E 2 inhibits OPN expression in SMCs, which is required for adventitial fibroblast migration involved in intimal thickening. 18 In addition, our data show that E 2 mediates the acceleration of endothelial repair through an OPN-dependent pathway suggesting dual opposite roles for OPN in SMCs and ECs, which both contribute to neointima inhibition.…”
mentioning
confidence: 99%